Efficacy and safety of catheter ablation for atrial fibrillation in patients with heart failure with preserved ejection fraction: a systematic review and meta-analysis - Chen, Xiaomei; Zhang, Xuge; Fang, Xiang; Feng, Shenghong (Frontiers in Cardiovascular Medicine, 2024)
Background Catheter ablation (CA) effectively treats atrial fibrillation (AF) in heart failure (HF) with reduced ejection fraction (HFrEF), improving clinical outcomes. However, its benefits for AF patients with heart failure with preserved ejection fraction (HFpEF)are still unclear. Methods We systematically searched PubMed, Embase, Web of Science, the Cochrane Library, and Scopus for studies investigating outcomes of CA in AF patients with HFpEF. Efficacy indicators included freedom from AF and antiarrhythmic drugs (AAD) free AF elimination. Safety indicators comprised total complications, HF admission, all-cause admission, and all-cause mortality. Sixteen studies with 20,796 patients included in our research. Results The comprehensive analysis demonstrated that, when comparing CA with medical therapy in HFpEF, no significant differences were observed in terms of HF admissions, all-cause admissions, and all-cause mortality ((OR: 0.42; 95% CI: 0.12–1.51, P=0.19), (HR: 0.78; 95% CI: 0.48–1.27, P=0.31), and (OR: 1.10; 95% CI: 0.83–1.44, P=0.51)) , while freedom from AF was significantly higher in CA (OR: 5.88; 95% CI: 2.99–11.54, P<0.00001). Compared with HFrEF, CA in HFpEF showed similar rates of freedom from AF, AAD-free AF elimination, total complications, and all-cause admission were similar ((OR:0.91; 95% CI: 0.71,1.17, P =0.47), (OR: 0.97; 95 % CI: 0.50–1.86, P =0.93), (OR: 1.27; 95% CI: 0.47–3.41, P =0.64), (OR: 1.11; 95% CI: 0.72, 1.73; P = 0.63)). However, CA in HFpEF was associated with lower rates of HF admission and all-cause mortality ((OR: 0.35; 95% CI: 0.20, 0.60; P=0.0002), (OR: 0.40; 95% CI: 0.18, 0.85; P =0.02)). Compared with patients without HF, CA in HFpEF patients exhibited lower rates of AAD-free AF elimination (OR: 0.48; 95% CI: 0.30, 0.75; P = 0.001). However, their rates of freedom from AF and total complications were similar ((OR: 0.70; 95% CI: 0.48, 1.02; P = 0.06), (OR: 0.60; 95% CI: 0.19, 1.90; P = 0.38)). Conclusion This meta-analysis conducted provided a comprehensive evaluation of the efficacy and safety of CA in patients with AF and HFpEF. The results suggest that CA may represent a valuable treatment strategy for patients with AF and HFpEF.